If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 3(x + 9) + -12 = 27 Reorder the terms: -6x + 3(9 + x) + -12 = 27 -6x + (9 * 3 + x * 3) + -12 = 27 -6x + (27 + 3x) + -12 = 27 Reorder the terms: 27 + -12 + -6x + 3x = 27 Combine like terms: 27 + -12 = 15 15 + -6x + 3x = 27 Combine like terms: -6x + 3x = -3x 15 + -3x = 27 Solving 15 + -3x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -3x = 27 + -15 Combine like terms: 15 + -15 = 0 0 + -3x = 27 + -15 -3x = 27 + -15 Combine like terms: 27 + -15 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| -3t+2(t-2)+6=-3 | | -9+5n+7= | | 2r+8-5= | | -2m-5-2(m-2)=3m-(4m-6)-5m+1 | | 2n+2(n+7)+1=39 | | 2y+2(y+1)=-6 | | 85+55x=y | | y=120+16(x) | | 2-6=a+a+4 | | -4p-3(4-3p)=2(p-4)-22 | | 3r+5(r-1)=27 | | 5(x+3)=8(x+6) | | 14x+12=4x^2 | | 4(r+6)=-49 | | -8x+48=-2(x-2)(x-2)+32 | | X+-1=0 | | -3(r+7)=-40 | | X+-2=0 | | 10(v+2)-2v=2(4v+3)-9 | | 2.87x+25.83=51.66 | | 5r^2=48+r | | -4(r+3)=-61 | | -10x+4=-7x+13 | | 9y-7=28 | | 6(x-2)=(x-4)-28 | | .3x+5=x+3 | | 18x-30= | | .3x+.5=1-0.05x | | f(X)=x^2+6x+1 | | (2x+10)+(6x-4)= | | -7-3y=14 | | 10+25b= |